A review of greywater characteristics and treatment processes - Boyjoo, Yash; Pareek, Vishnu; Ang, Ha Ming (International Association on Water Quality, 2013)
This paper presents a comprehensive literature review of different characteristics of greywater (GW) and current treatment methods. GW is domestic wastewater excluding toilet waste and can be classified as either low-load GW (excluding kitchen and laundry GW) or high-load GW (including kitchen and/or laundry). This review provides information on the quantity of GW produced, its constituents (macro and micro), existing guidelines for wastewater reuse, current treatment methods (from storage to disinfection) as well as related costs and environmental impacts. Moreover some successful examples from various countries around the world are examined. The current preferred treatments for GW use physical and biological/natural systems. Recently, chemical systems like coagulation, adsorption and advanced oxidation processes (AOPs) have been considered and have been successful for low to moderate strength GW. The presence of xenobiotic organic compounds (XOC), which are hazardous micropollutants in GW, is emphasised. Since conventional treatments are not efficient at removing XOC, it is recommended that future studies look at chemical treatment, especially AOPs that have been found to be successful at mineralising recalcitrant organic compounds in wastewater.